A study to evaluate the immunogenicity and shedding of live attenuated influenza vaccine strains in children 24–<48 months of age. Issue 5 (29th January 2020) - Mallory, Raburn M.; Nyborg, Andrew; Kalyani, Rubana N.; Yuan, Yuan; Block, Stan L.; Dubovsky, Filip
Highlights: Live attenuated influenza vaccine H1N1 strain A/Bolivia had reduced effectiveness. Novel assays identified H1N1 strain with improved replicative fitness (A/Slovenia). More children shed the A/Slovenia vaccine strain than the A/Bolivia strain. A/Slovenia strain had improved immunogenicity versus the A/Bolivia strain. A/Slovenia immune responses comparable to efficacious pre-pandemic H1N1 strain. Abstract: Background: Quadrivalent live attenuated influenza vaccine (LAIV4) showed reduced effectiveness against the A/H1N1 component in the 2013–2014 and 2015–2016 influenza seasons. The most likely cause of reduced LAIV effectiveness against A(H1N1)pdm09 strains was poor intranasal replication. Objectives: To compare the immunogenicity and shedding of a new A/H1N1 strain (A/Slovenia), to a A/H1N1 strain known to have reduced effectiveness (A/Bolivia). Patients/methods: This was a randomized, double-blind, multicenter study. Children aged 24–<48 months of age were randomized 1:1:1 to receive two doses of LAIV4 2017–2018 (LAIV4A/Slovenia ), or LAIV4 2015–2016 or trivalent LAIV (LAIV3) 2015–2016 formulations (LAIV4A/Bolivia or LAIV3A/Bolivia, respectively) on days 1 and 28. The primary endpoint was strain-specific hemagglutination inhibition (HAI) antibody seroresponse at 28 days post each dose, and secondary endpoints included immunogenicity, shedding, and safety. Solicited symptoms, adverse events (AEs), and serious AEs (SAEs) were recorded. Pre-specified statistical testing was limited to the primary endpoint of HAI antibody responses. Results: A total of 200 children were randomized (median age 35.3 months; 53% male; 57% had previously received influenza vaccine). Significantly higher HAI antibody responses for the A/Slovenia strain were observed after Dose 1 and Dose 2. Neutralizing antibodies and nasal immunoglobulin A antibody responses were higher for A/Slovenia versus A/Bolivia. More children shed the A/Slovenia vaccine strain than the A/Bolivia strain on Days 4–7 after Dose 1. No deaths, SAEs, or discontinuations from vaccine occurred. Conclusions: The new A(H1N1)pdm09 A/Slovenia LAIV strain demonstrated improved immunogenicity compared with a previous strain with reduced effectiveness and induced immune responses comparable to a highly efficacious pre-pandemic H1N1 LAIV strain. These results support the use of LAIV4 containing A/Slovenia as a vaccine option in clinical practice.